2017
DOI: 10.1186/s13014-017-0788-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypo- or conventionally fractionated radiotherapy combined with chemotherapy in patients with limited stage small cell lung cancer

Abstract: BackgroundPrevious data from our institution showed that hypofractionated thoracic radiotherapy (HypoTRT) with concurrent etoposide/platinum chemotherapy yielded favorable survival in patients with limited-stage small cell lung cancer (LS-SCLC). The present study retrospectively compared the survival outcomes, failure patterns and toxicities between groups of LS-SCLC patients treated with conventionally fractionated thoracic radiotherapy (ConvTRT) or HypoTRT combined with chemotherapy.MethodsMedical records of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
(27 reference statements)
3
13
2
Order By: Relevance
“…[33][34][35][36] Zhang et al and Videtic et al concluded that HFRT and CFRT regimens yield similar OS, local control, treatment failure patterns, and toxicity outcomes, corroborating our findings. 33,34 Bettington et al suggested that 40 Gy in 15 fractions and 45 Gy in 30 fractions, given twice daily, provided equivalent relapse-free survival rates. 36 Turgeon et al only described local control and OS rates in 68 patients treated with 40 Gy in 16 fractions, with no comparison or control group.…”
Section: Discussionsupporting
confidence: 90%
“…[33][34][35][36] Zhang et al and Videtic et al concluded that HFRT and CFRT regimens yield similar OS, local control, treatment failure patterns, and toxicity outcomes, corroborating our findings. 33,34 Bettington et al suggested that 40 Gy in 15 fractions and 45 Gy in 30 fractions, given twice daily, provided equivalent relapse-free survival rates. 36 Turgeon et al only described local control and OS rates in 68 patients treated with 40 Gy in 16 fractions, with no comparison or control group.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study the median PFS was 16.7 months (95% CI, 6.7 -19.0 months), and 1-, and 2-years PFS rates were 60%, and 41.4%, respectively, when compared to the study by Zhang et al [30], where the median PFS was 18.2 months (95% CI: 15.8 -20.6 months), and the 1-year and 2-year PFS rates were 64.8% and 32.4%, respectively. The median OS in our study was 26.4 months (95% CI, 10.4 -28.1 months), and 1-, and 2-years OS rates were 78% and 58.3%, compared to the results of the study by Zhang et al [30], where the median OS was 27.2 months (95% CI: 25.2 -29.2 months), and the 1-and 2-year survival rates were 87.0% and 62.2%, respectively. As a natural behavior of SCLC, distant metastasis was reported to be the most common pattern of failure which occurred in 50% of the patients in our study, while 17% patients developed locoregional recurrence.…”
Section: Discussioncontrasting
confidence: 58%
“…In the current study ORR was reported to be 90%, while in a similar trial done by Zhang et al in the HYPO-RT arm, ORR was 97% [30]. In the current study the median PFS was 16.7 months (95% CI, 6.7 -19.0 months), and 1-, and 2-years PFS rates were 60%, and 41.4%, respectively, when compared to the study by Zhang et al [30], where the median PFS was 18.2 months (95% CI: 15.8 -20.6 months), and the 1-year and 2-year PFS rates were 64.8% and 32.4%, respectively. The median OS in our study was 26.4 months (95% CI, 10.4 -28.1 months), and 1-, and 2-years OS rates were 78% and 58.3%, compared to the results of the study by Zhang et al [30], where the median OS was 27.2 months (95% CI: 25.2 -29.2 months), and the 1-and 2-year survival rates were 87.0% and 62.2%, respectively.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Subgroups of patients with an especially high risk of early distant metastases are clearly identifiable. Examples include those with limited-stage small-cell lung carcinoma 129 , locally advanced pancreatic ductal adenocarcinoma 130 or colorectal cancer and resectable liver metastases 131 . These disease settings are attractive both commercially and clinically, although reliance on such populations for early go versus no-go decisions holds the risk that effective anti-metastatic drugs will be prematurely discarded.…”
Section: Challenges In Clinical Trial Designmentioning
confidence: 99%